PORTRAIT OF FEMALE HERO IMAGES IN ANCIENT TURKISH SOURCES (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the image of female characters reflected in ancient Turkish sources, in particular, in “Avesta”. It highlights the social, spiritual and moral status of women in society, their role as mothers, educators, protectors and wise persons. Also, the connection of women with nature, fertility and goodness is revealed in the example of goddesses such as Ardvisura Anahita, mythological female characters. The article analyzes the elements of respect for women, gender equality and their role in the development of society in ancient sources on a scientific basis.
Keywords: “Avesta”, female image, ancient Turkic sources, mythology, Ardvisura Anahita, goddess, mother image, gender equality, spirituality, moral values, folklore, ancient beliefs.